Gambaran Risiko Penyebaran Penyakit Diare Melalui Vektor Lalat Berdasarkan Kondisi Sanitasi Lingkungan di Pasar Tradisional X Indrapura Kabupaten Batu Bara - Meutia Nanda; Jihan Fadhillah; Najwa Azzahra; Fidelma Felicia; Sarah Agustina (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Diarrhea remains a public health problem closely associated with environmental sanitation conditions. In Batu Bara Regency, 3,382 cases of diarrhea were reported in 2025. This study aimed to analyze the risk of diarrhea transmission through fly vectors based on environmental sanitation conditions at X Indrapura Traditional Market. This study employed a descriptive quantitative observational method with a cross-sectional approach through direct observation using a sanitation checklist and fly density measurements. The results showed that the vegetable section had a sanitation score of 52.5% (fair category), while the grocery section scored 77.5% (good category). The highest average fly density was found in the fish section (13.8 flies), followed by the vegetable section (10.6 flies) and the grocery section (3.4 flies). Higher fly density was observed in areas with large amounts of organic waste, humid conditions, and inadequate drainage systems. Poor sanitation conditions may increase fly populations, thereby raising the risk of food contamination and diarrhea transmission. Therefore, improvements in waste management, sanitation facilities, and vector control are needed to create a healthier market environment.